Analysis of Dark Signal Degradation Caused by 1 MeV Neutron Irradiation on Backside‐Illuminated CMOS Image Sensors. Issue 1 (1st January 2021) - Bingkai, Liu; Yudong, Li; Lin, Wen; Dong, Zhou; Jie, Feng; Xiang, Zhang; Yulong, Cai; Jing, Fu; Qi, Guo
Abstract : The purpose of this work is to investigate the influence of the epitaxial layer thickness of Backside‐illuminated CMOS image sensors (BSI CISs) on dark signal behaviors. BSI CISs with the high quantum efficiency and sensitivity were irradiated by 1 MeV neutron up to the fluences of 10 9 cm ‐2 . The displacement damage induced variations of the mean dark signal, Dark signal nonuniformity (DSNU), dark signal spikes and Random telegraph signal (RTS) on the different epitaxial layer thicknesses are analyzed. The experimental results show that there is no obvious correlation between the degradations of dark signal parameters and the epitaxial layer thickness, suggesting that the electric‐optical performance of BSI CISs can be improved by optimizing the epitaxial layer thickness.